PENCEGAHAN PEREDARAN NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II B BANGKINANG OLEH APARAT LEMBAGA PEMASYARAKATAN - Ardian Syahputra; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The misuse and illicit trafficking of narcotics in Indonesia has spread throughout the country andhas been spread in various living environments, both the educational environment, the work environment,and the residential environment, and the law enforcement environment. One law enforcement agency that isalso not free from drug abuse and illicit trafficking is a penitentiary. Correctional Institution is a place tocarry out the formation of prisoners and correctional students based on the penal system. As a regulationfor the implementation of the Penal Act, a Minister of Law and Human Rights Regulation No. 6/2013 wasissued concerning the Standing Orders of State Correctional Institutions and Detention Centers Article 4letter (g) The Ministerial Regulation prohibits every prisoner or detainee from storing, making, carrying,distributing, and / or consuming narcotics and / or narcotics precursors and other dangerous drugs. Thepurpose of writing this thesis, namely: First, to determine the efforts of prison officials in preventingNarcotics circulation in Class II B correctional facilities in Bangkinang. Second, to find out the obstacles ofcorrectional institutions in preventing Narcotics circulation in Class II B correctional facilities inBangkinang.This type of research can be classified as a type of sociological legal research, because in thisstudy the authors directly conduct research on the location or places that are studied to provide a completeand clear picture of the problem under study. This research was conducted at Class II B Penitentiary inBangkinang, while the population and sample were all sections related to this study, data sources usedwere, among others, primary data, secondary data, and tertiary data, data collection techniques namelyinterview and study literature.From the results of research and discussion it can be concluded that, First, the efforts ofcorrectional institutions in preventing Narcotics circulation in prison are to maximize searches by carryingout luggage checks and data collection conducted on visitors and taking action for all people enteringPenitentiary Class II B Bangkinang without exception. . Secondly, the inhibiting factor of the efforts ofprison officials in preventing Narcotics circulation in Bangkinang Class II B Penitentiary is inadequatefacilities and infrastructure, lack of female prison wardens, lack of prison staff knowledge about narcotics.Keywords: Circulation - Narcotics – Penitentiary